An inter-institutional collaboration: transforming education through interprofessional simulations. Issue 5 (16th May 2013) - King, Sharla; Drummond, Jane; Hughes, Ellen; Bookhalter, Sharon; Huffman, Dan; Ansell, Dawn
Abstract: An inter-institutional partnership of four post-secondary institutions and a health provider formed a learning community with the goal of developing, implementing and evaluating interprofessional learning experiences in simulation-based environments. The organization, education and educational research activities of the learning community align with the institutional and instructional reforms recommended by the Lancet Commission on Health Professional Education for the 21st century. This article provides an overview of the inter-institutional collaboration, including the interprofessional simulation learning experiences, instructor development activities and preliminary results from the evaluation.